Administrative Aspects of Public Electronic Services - Kirilova, Katia (Research Papers, 2019)
The article presents some of the administrative aspects in creating new public e-services. The main aim is to propose changes in the direction of improvement and digitization of the main administrative processes on the basis of the provided public electronic services to the students in relation to their career development. The tasks are related to the clarification of the characteristics of the existing public electronic services for career development and proposals for changes in the main administrative processes. The results achieved are in the direction of clarifying the strengths of the e-portfolio as an element of the career development of the students and a proposal for a specific technological realization.
Keywords: Administrative services; Public services; E-government